The evolution of predator avoidance in cephalopods: A case of brain over brawn? - Jaitly, Rahul; Ehrnsten, Eva; Hedlund, Johanna; Cant, Michael; Lehmann, Philipp; Hayward, Alexander (Frontiers in Marine Science, 2022)
Predation is a major evolutionary driver of animal adaptation. However, understanding of anti-predator evolution is biased toward vertebrate taxa. Cephalopoda, a class in the invertebrate phylum Mollusca, are known for their diverse anti-predator strategies, characterised by their behavioural flexibility. While ancestral cephalopods were protected by a hard outer shell, extant cephalopods have greatly reduced their reliance on physical defences. Instead, cephalopods have evolved highly developed senses to identify potential threats, cryptic skin patterns to avoid detection, startle responses to deter attack, and elaborate means of escape. While cephalopod anti-predator repertoires are relatively well described, their evolution, and the selective pressures that shaped them, have received much less attention. This is despite their potential relevance, in turn, to elucidate evolution of the remarkable cognitive abilities of cephalopods. Here, we review cephalopod anti-predator evolution, considering four key aspects: (i) shell reduction and loss; (ii) the skin patterning system; (iii) the ecological context accompanying the evolution of advanced cognitive abilities; (iv) why the evolutionary trajectory taken by cephalopods is so unique among invertebrates. In doing so, we consider the unique physiology of cephalopods and discuss how this may have constrained or aided the development of their anti-predator repertoire. In particular, cephalopods are poorly equipped to defend themselves physically and escape predation by fish, due to a lack of comparable weaponry or musculature. We argue that this may have selected for alternative forms of defence, driving an evolutionary trajectory favouring crypsis and complex behaviours, and the promotion of sensory and cognitive adaptations. Unravelling the complexities of cephalopod anti-predator evolution remains challenging. However, recent technological developments available for cephalopod field and laboratory studies, coupled with new genomic data and analysis approaches, offer great scope to generate novel insights.